Pengaruh Akhlak dan Spiritual Remaja Terhadap Konsep Diri Remajadi Kabupaten Seluma - Monika, Nales; Yuganda, Yuganda; Puri Wulandari, Yora; Kenneth Michael Baba (DAWUH : Islamic Communication Journal, 2023)
This research aims to find out or see the influence of morals and spirituality on self-concept among teenagers in Seluma Regency. In this research, researchers used a quantitative approach, the sample collection technique in this research was the Cluster Random Sampling technique and direct data collection. The research subjects were 111 respondents, namely teenagers in Seluma Regency. From the results of the research, the researchers showed that of the 111 respondents, the influence of morals and spirituality on the self-concept of teenagers in Seluma Regency was very weak, namely 5.1%, meaning that the weaker a person's spiritual morals, the lower the self-concept of teenagers.